Effects of long-term endurance and resistance training on diastolic function, exercise capacity, and quality of life in asymptomatic diastolic dysfunction vs. heart failure with preserved ejection fraction - Nolte, Kathleen; Schwarz, Silja; Gelbrich, Götz; Mensching, Steffen; Siegmund, Friederike; Wachter, Rolf; Hasenfuss, Gerd; Düngen, Hans Dirk; Herrmann-Lingen, Christoph; Halle, Martin; Pieske, Burkert; Edelmann, Frank (ESC Heart Failure, 2014)
Background: The long-term effects of exercise training (ET) in diastolic dysfunction (DD) and heart failure with preserved ejection fraction (HFpEF) are unknown. The present study compared the long-term effects of ET on exercise capacity, diastolic function, and quality of life (QoL) in patients with DD vs. HFpEF. Methods: A total of n = 43 patients with asymptomatic DD (n = 19) or HFpEF [DD and New York Heart Association (NYHA) ≥II, n = 24] and left ventricular ejection fraction ≥50% performed a combined endurance/resistance training over 6 months (2–3/week) on top of usual care. Cardiopulmonary exercise testing, echocardiography, and QoL were obtained at baseline and follow-up. Results: Patients were 62 ± 8 years old (37% female). In the HFpEF group, 67% of patients were in NYHA class II (33% in NYHA III). Exercise capacity (peak oxygen consumption, peak VO2) differed at baseline (DD 29.2 ± 8.7 mL/min/kg vs. HFpEF 17.8 ± 4.6 mL/min/kg; P = 0.004). After 6 months, peak VO2 increased significantly (P < 0.044) to 19.7 ± 5.8 mL/min/kg in the HFpEF group and also in the DD group (to 32.8 ± 8.5 mL/min/kg; P < 0.002) with no overall difference between the groups (P = 0.217). E/e′ ratio (left ventricular filling index) decreased from 12.2 ± 3.5 to 10.1 ± 3.0 (P < 0.002) in patients with HFpEF and also in patients with DD (10.7 ± 3.1 vs. 9.5 ± 2.3; P = 0.03; difference between groups P = 0.210). In contrast, left atrial volume index decreased in the HFpEF group (P < 0.001) but remained stable within the DD group (difference between groups P = 0.015). After 6 months, physical QoL (Minnesota living with heart failure Questionnaire, 36-item short form health survey), general health perception, and 9-item patient health questionnaire score only improved in HFpEF (P < 0.05). In contrast, vitality improved in both groups (difference between groups P = 0.708). Conclusion: A structured 6 months ET programme effectively improves exercise capacity and diastolic function in patients with DD and overt HFpEF. Therefore, controlled lifestyle modification with physical activity is effective both in DD and HFpEF.
CRIS-Team Scopus Importer:2023-03-08
Keywords: Diastolic dysfunction; Exercise training; Heart failure with preserved ejection fraction